The Weblight-District : a study of how women use the internet to work independently as sex workers, their investments in this kind of work, and the challenges this poses - Van Rooi, Wildo Alvir (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.